Synthesis and Cytotoxic Effects of Various Thiosemicarbazide Compounds on Primary and Metastatic Breast Cancer Cell Lines - Ensarioglu, Hilal Kabadayi; Becer, Eda; Basoglu, Faika; Guzeldemirci, Nuray Ulusoy; Vatansever, Hafize Seda (Galenos Publ House, 2025)
BACKGROUND/AIMS: Thiosemicarbazides and their metal complexes are known for their antiviral, antibacterial, and antitumor properties. This research describes the synthesis of four novel thiosemicarbazide derivatives (5, 8, 13, and 14) and investigates their cytotoxic effects on primary (MCF-7) and metastatic (M4A4) breast cancer cells. The study explored the Wnt/beta-catenin signaling pathway as well as key factors associated with proliferation, and stemness, that play a vital role in breast cancer development. MATERIALS AND METHODS: Hydrazide derivatives containing imidazo[2,1-b]thiazole ring were synthesized through a conventional method. The MCF-7 and M4A4 cells were cultivated and exposed to different concentrations (200 mu M, 400 mu M, 800 mu M) of the all compounds for 24 and 48 hours. Cytotoxicity was investigated using the 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay. The distribution of beta-catenin, GSK 3 beta, LGR5, Wnt 5a, Ki-67, Cxcl1, and CD44 were analyzed using indirect immunoperoxidase staining. RESULTS: A 200 mu M dose for all compounds for 24 hours was selected based on MTT assay for further analyses. Immunohistochemical analysis exhibited that compounds 5, 8, and 14 stimulated the Wnt/beta-catenin pathway in both cell lines, with an elevation in the immunoreactivity of beta-catenin, GSK 3 beta, and LGR5 also observed. Compound 13 reduced the proliferation of M4A4 cells, but an increase in stemness was also observed. CONCLUSION: Various thiosemicarbazide compounds affected primary and metastatic breast cancer cell lines differently. Among these, compound 13 showed an ability to reduce the growth of metastatic breast cancer cells. However, additional research about the stemness properties of breast cancer should be evaluated in further investigations.
Keywords: Thiosemicarbazide; Wnt/ beta -catenin; stemness; breast cancer